Teaching Work in and for School: relationships between Extra-Class Days and Professional Development (Revista Internacional de Formação de Professores, 2024)
This article presents part of the results of the research on the relationships between teaching work and extracurricular work, developed in two schools in the interior of Bahia. The research had as theoretical assumptions the Bakhtinian philosophy of language and the concepts of professional development. In addition to the bibliographical review, a Circle of Intertwined Voices (CVE) was held with effective school teachers to understand the circulation of teaching voices in the discursive process, established in 72 meetings focusing on the extra-class day. The results showed a demand to fulfill a program, almost always, disjointed from what is desired to be developed; teaching work subjugated to a routine, without valuing the teaching experience; teaching work is dynamic, authorial, continuous, adaptive and multi-sapient; necessary resizing of teaching work through actions that value creativity and authorship; the extra-class day should encourage discussions and planning of pedagogical actions. A professional development plan, within the scope of the extra-class day, reconfigures work in and with the school, aiming for continued teacher training.
Keywords: Teaching Work. Professional development. Extra-class Day. Teacher Training. Education.